Primary CNS Lymphoma Arising from the 4th Ventricle: A Case Report and Review of the Literature - Ava Brozovich; Donald Ewing; Ethan Burns; Courtney Hatcher; Gonzalo Acosta; Usman Khan; Betty Chung; Leena Samuel; Jasleen Randhawa; Sai Ravi Pingali (Case Reports in Oncological Medicine)
A 65-year-old male with a history of ischemic strokes, seizures, and subarachnoid hemorrhage presented with a 4-week history of progressive diplopia, vertigo, nausea, and vomiting. Magnetic resonance imaging (MRI) revealed a 2.5×1.8×1.7 cm posterior fossa mass arising from the roof of the 4th ventricle extending into the cerebellar vermis. Posterior fossa craniotomy with stereotactic biopsy confirmed a locally invasive diffuse large B-cell lymphoma (DLBCL). Primary central nervous system lymphoma (PCNSL) arising from the 4th ventricle is a rare extranodal manifestation of non-Hodgkin lymphoma (NHL), with few cases documented in the literature. Review of available cases lends support that lymphoma arising from the 4th ventricle has a variable clinical presentation, occurs most commonly in immunocompetent males, and should be on the differential of any immunocompetent adult presenting with a posterior fossa mass. Optimal treatment modalities are based largely on phase 2 clinical trials, and recommended guidelines regardless of anatomic location should be adhered to.